La Autoestima en el Desarrollo Socio Emocional en niños de 4 A 5 Años - Yauli Chicaiza, Karen Jahayra (2022)
The present investigation reveals the importance of self-esteem, determining relevant aspects in socio-emotional development, in children of Initial Education of the "Luis Fernando Ruiz" Educational Unit, adding to this it aims to help foster affective bonds, providing a theoretical support based on the importance of the personal training of children and the little information that teachers and parents have, to improve self-esteem in the classroom because self-esteem becomes the basis of the development of the personality of boys and girls, and learning depends on their level of self-esteem, the activities carried out and the process of building the safe well-being of each child during their childhood. This research work has a qualitative approach that allowed to collect data and analyze variables. In addition, the methodology used for the characteristics of the research was qualitative, the deductive scientific method was taken as a basis, because it was based on existing theories, as well as a bibliographic and field type, such as data collection techniques and instruments. information was used the interview that was applied to the teacher, in the same way the surveys were carried out to the parents, through the observation sheet applied to the children it can be examined and deduced that it is pertinent that the teachers must be constantly updating their knowledge to strengthen emotions according to modern needs and current education, so that negative emotions do not hinder the comprehensive development of infants and provide children with a quality and warm education.